Determination of the actual accuracy of GNSS positioning using a total station for monitoring landslide processes - V.V. Korobiichuk; D.V. Mitchenko (Технічна інженерія)
The aim of the study is to determine the actual accuracy of GNSS positioning using a total station in existing landslide zones. The article presents an assessment of the actual GNSS positioning accuracy by comparing its results with data obtained from a total station. The research is conducted in the context of monitoring landslide-prone areas, where coordinate accuracy is critically important to prevent emergency situations. The study considers the main factors influencing GNSS measurement accuracy, including geodetic conditions, types of receivers used, presence of obstructions, and software characteristics.